Effects of whole blood leukoreduction on platelet function and hemostatic parameters. Issue 5 (5th August 2019) - Morris, M. C.; Veile, R.; Friend, L. A.; Oh, D.; Pritts, T. A.; Dorlac, W. C.; Spinella, P. C.; Goodman, M. D.
SUMMARY: Aims/Objectives: The aim of this study was to evaluate the hemostatic consequences of whole blood leukoreduction (LR). Background: Whole blood is being used for trauma resuscitation in the military, and an increasing number of civilian trauma centres across the nation. The benefits of LR, such as decreased infectious and transfusion‐related complications, are well established, but the effects on hemostatic parameters remain a concern. Methods: Twenty‐four units of whole blood were assigned to one of the four groups: non‐leukoreduced (NLR), leukoreduced at 1 h and a height of 33 in. (LR‐1), leukoreduced at 4 h and a height of 33 in. (LR‐4(33)), or leukoreduced at 4 h and a height of 28 in. (LR‐4(28)). Viscoelastic parameters, platelet aggregation, cell counts, physiological parameters and thrombin potential were evaluated immediately before and after LR, and on days 1, 7, 14 and 21 following LR. Results: The viscoelastic parameters and thrombin generation potential were unchanged between the groups. Platelet aggregation was reduced in the LR‐1 group compared with NLR after 7 days. The LR‐4(28) group also showed a trend of reduced platelet aggregation compared with NLR. Aggregation in LR‐4(33) was similar to NLR throughout the storage time. Physiological and electrolyte changes over the whole blood storage period were not affected by LR. Conclusion: Our study shows that whole blood can be LR at 4 h after collection and a height of 33 in. while maintaining platelet count and without altering platelet function and hemostatic performance.